Compliance With the Worker’s Compensation Act in Ugandan Industries: An Anlytical Review of Legal Framework and Implementation Practices - Joan Nalumu (Uganda Christian University, 2024)
This abstract presents a brief study of Worker's Compensation Act compliance in Ugandan industries, with an emphasis on both the legal framework and actual implementation strategies. The Workers’ Compensation Act is an important legislative instrument in Uganda that protects workers' rights and well-being by providing compensation for work-related injuries, disabilities, or fatalities. The Workers’ Compensation Act legislative framework outlines employers' and employees' rights and obligations in terms of compensation, dispute resolution, and consequences for noncompliance. However, difficulties exist in converting these legal principles into successful implementation techniques in industrial environments One of the main barriers to compliance is the lack of knowledge and comprehension of the Workers’ Compensation Act among employees and employers, especially in small and medium-sized businesses (SMEs). Additionally, ineffective bureaucratic efficiency, oversight, and inspection capabilities of enforcement mechanisms lead to unchecked instances of non-compliance. A multifaceted strategy is needed to address these issues, including improved enforcement tactics, heightened public awareness efforts, and assistance for SMEs to adhere to the Workers’ Compensation Act. Uganda may strengthen the legal framework and improve implementation techniques to improve worker protection and promote sustainable economic growth.